Interactions in Visualization - Ganuza, María Luján (2018)
The overall goal of this thesis is to define the interactions and a classification of interactions in visualization valid in different application domains. The defined interactions will be applied to the states and transformations of the visualization process. In this context, it is necessary to define a representation for the data sets involved in the process. This representation must be sufficiently flexible to support the different classifications of data, attributes, data sets and visual mappings present in the visualization literature.